Pengembangan Sumber Daya Manusia di Area Lingkar Tambang Pt. Berau Coal melalui Pelatihan Kampung Wisata - Khairu Farras Shidqi; Hary Hermawan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Human Resources Development in the Mine Circle Area PT. Berau Coal through Tourism Village Training Tourist visits to Berau Regency are expected to increase from 2010 to 2021. therefore, human resources must be carefully prepared to support smooth tourism activities, which PT Berau Coal is doing through its Corporate Social Responsibility (CSR) program and PPM (Community Empowerment and Development) activities. Community service will be conducted on human resources development in the Mine Circle Area of PT. Berau Coal through the Tourism Village Training by identifying HR competencies before and after the tourism village training and identifying the supporting and inhibiting factors for the training's implementation. Tourism village training was held, and community readiness increased as a result, as well as the supporting and inhibiting factors in this activity.